Sistem Informasi Kearsipan Tata Kelola Surat Pada Kantor Inspeksi BRI Kota Padang - Yanni Suherman (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2017)
A letter is a means to submit a statement or information in writing from one party to another. The information may be a notice, statement, request, report, thought, rebuttal and so on. The management of letters within an institution is categorized into two, namely incoming and outgoing mail. An incoming letter is a letter received by an organization / institution made by another official organization / institution and an outgoing letter is a letter sent by an organization / institution made by another official organization / institution. BRI Inspection Office is representative of BRI directors in regions that perform supervisory function of operational working units in the region, or it can be said is the eyes and ears of directors in the region. Including the Inspection Office of BRI Padang City, which oversees the operational work units located in the Padang City area and conducts audits with the aim of ensuring that internal controls in the operational work units in their working areas are effective especially in Padang City. In the mail archiving system, there are many piles of unorganized letters so that when supervisors want to check incoming mail or outgoing mails they will not be properly managed. This new letter governance information system is expected to make it easier for the BRI Inspection Office to manage the archiving of incoming and outgoing mail.